2023
DOI: 10.1007/s00432-023-04642-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analyses of bulk microarray data to discover genes, pathways, and immune infiltration characteristics associated with targeting of Ewing sarcoma

Abstract: Purpose To explore transcriptome and immunological features of patients with Ewing sarcoma (ES) using all publicly available microarray data. Methods Data of 479 ES tissues were integrated and normalized. Gene expression, immune infiltration, and cancer-specific pathways were analyzed. Genes of interest were knocked down, followed by cell proliferation and colony formation assays. Results Consistent with the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Genes encoding nuclear proteins such as HIST1H4C, H2AFZ, CENPF, and CKS2, which interact with cell-cycle regulatory proteins, were among the most highly expressed genes in these two clusters (Figure 2C, File S1). Of interest to us is the fact that these genes have been recognized as exclusive biomarkers for cell proliferation associated with a higher S and G2M score, suggesting functions in growth and cell division [71][72][73]. Moreover, TOP2A and CENPF, markers for cell-cycle regulation that were among the exclusively expressed genes in the proliferating S and G2M clusters, are reported to synergistically promote cell division, epithelial-mesenchymal transition (EMT), proliferation, and migratory phenotypes [74].…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding nuclear proteins such as HIST1H4C, H2AFZ, CENPF, and CKS2, which interact with cell-cycle regulatory proteins, were among the most highly expressed genes in these two clusters (Figure 2C, File S1). Of interest to us is the fact that these genes have been recognized as exclusive biomarkers for cell proliferation associated with a higher S and G2M score, suggesting functions in growth and cell division [71][72][73]. Moreover, TOP2A and CENPF, markers for cell-cycle regulation that were among the exclusively expressed genes in the proliferating S and G2M clusters, are reported to synergistically promote cell division, epithelial-mesenchymal transition (EMT), proliferation, and migratory phenotypes [74].…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al found that NKX2-2-AS1 was highly expressed in Ewing sarcomas, functioning as a core co-regulator of the driver mutation fusion gene, and is recognized as a specific biomarker for Ewing sarcomas [ 26 ]. Muraguchi et al described that NKX2-2 suppresses the self-renewal of glioma-initiating cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%